The Loyal, True, and Brave: America's Civil War Soldiers - Woodworth, Steven E. (Rowman & Littlefield Publishers, 2002)
Courage, perseverance, and dedication were hallmarks of the Civil War soldier. These qualities, along with their disarming humanness, have lent an enduring attraction to their story. In The Loyal, True, and Brave: America's Civil War Soldiers, readers will learn how the soldier's story has changed over the years, being told in different ways as passing generations introduced their own questions and interests. Steven Woodworth weaves together a variety of writings—by historians and by Civil War soldiers themselves—so that readers are presented with a lively, balanced picture of all the major aspects of the Civil War soldier's life. Woodworth presents the experiences of both Union and Confederate soldiers so readers gain equal perspective on the men who enlisted for North and South. The Loyal, True, and Brave contains detailed descriptions of every facet of the soldier's life, including enlistment, combat, hospitals, prison, and camp life. Included are writings by Civil War soldiers Abner R. Small, an officer in a Maine regiment; John C. Reed, a lawyer-planter from Georgia and member of the 8th Georgia; and German immigrant Johann Stuber of the 58th Ohio. Renowned historians Reid Mitchell, Bell I. Wiley, James M. McPherson, Earl J. Hess, and Gerald F. Linderman are also featured. Each chapter begins with an introduction by Woodworth, discussing the general topic of that chapter and the historiographical issues involved. These selections offer the best brief introduction available on Civil War soldiers and the historians who have written about them.The Loyal, True, and Brave is ideal for courses on the Civil War and Reconstruction, American nineteenth-century history, and American social and cultural history.